Towards a Conceptual Framework Supporting Model Compilability - Chiorean, Dan; Petrascu, Vladiela (Electronic Communications of the EASST, 2010)
The ever-growing use of modeling languages today is largely due to a maturation of model-based development technologies. However, there is enough room for improving language specifications and consequently, the efficiency of their usage. The state of facts in specifying Well Formedness Rules is among the most important issues calling for improvements. Despite the fact that various papers have approached it, the topic is still open. To solve it, there is the need of a rigorous conceptual framework supporting the specification of modeling languages’ static semantics. This would stand as a basis for ensuring model compilability, a mandatory requirement in a model-driven context. Through this paper, we aim at providing core ideas that would contribute to the creation of such a framework. Our approach is testing-oriented and promotes the use of OCL specification patterns.